Trade expansion and economic integration among developing countries - United Nations Conference on Trade and Development (New York : United Nations, 1967)
The UNCTAD secretariat considered it useful not only to state in this report what, ideally, ought to be done, but has given detailed attention to the practical negotiating problems which developing countries are likely to encounter when they try to apply the various measures for expanding trade with each other.
"United Nations publication. Sales no.: 67.II.D.20."
Includes bibliographical references.
osc 31/10/2018
Loans
Keywords: International economic integration; Developing countries